Conformational and Topology Analysis of Diphenylthiourea and Diarylhalidethiourea Compounds Using DFT - Nur Najwa-Alyani Mohd Nabil; Lee Sin Ang (Universitas Gadjah Mada, 2020)
The disubstituted thiourea compounds have shown its reliability on their usages in various industries compared to the thiourea compounds. However, they also show capability to exist in different configurations, which would render them to possess different properties and hence affect their usability by unsuspected users. In this study, investigation was carried out on the polymorphism of five disubstituted thiourea compounds in which the phenyl rings and arylhalide acted as substituents. Using the B3LYP/DEF2–TZVP model chemistry with D3–BJ and gCP correctional schemes, the energetic analysis on the possible structural arrangements of the compounds was performed. The topology analysis of non-covalent interaction and electrostatic potential surfaces was used for understanding the interaction and reactivity of the constitute molecules of the compounds. Energetic results show that for all interested compounds, CT and TT configurations may coexist. Between the two type of substituents, phenyl substituted molecules are more flexible with better capability to be nucleophilic compound. On the other hand, the arylhalide substituted molecules form better electrophilic compounds. The reactive sites of the molecules rotated to the stable new configurations are similar to the molecules in their original configurations observed from experiments.